PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL BERBASIS KONTEKSTUAL PADA MATA PELAJARAN PAI KELAS VII - Junaidi Junaidi; Djuwairiyah Djuwairiyah; Minhaji Minhaji (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2023)
Contextual learning media is not much developed by PAI teachers. In addition, there are limitations of teacher competencies to develop creative learning media for students. Therefore, this study aims to describe the design specifications of digital comic learning media with a contextual approach in improving student learning outcomes in class VII PAI subjects. After that, the second goal is to find out the feasibility of digital comic learning media with a contextual approach from material experts and media experts. This research method uses a research and development approach. The research model used is Analyze, Design, Develop, Implementation and Evaluation. Data collection was obtained through observation, documentation, interviews, and validation instruments. The results of this study indicate that the design specifications for digital comic learning media discuss religious material that requires contextual explanation, in this case, honest, trustworthy, and consistent material. The output of learning media can be used via a smart phone based on the Android system. The feasibility of comics from the material aspect obtains a very feasible category with a mode of 84.7%. While the feasibility of comics in the media aspect is smaller than the feasibility of the material, arround 80%, but it is still a proper level using in learning. Through a sufficiently mature initial study and recommendations for the feasibility of comic media from experts, it is strongly predicted that this learning media can improve learning outcomes for class VII junior high school students with contextual-based learning